Modelling of vibration-damping properties of elastic-viscoplastic layers of the roadbed. Problem statement 2 - V. M. Bel’Kov (Вестник Научно-исследовательского института железнодорожного транспорта)
The present article is a continuation of the article [1], where was considered a model of the vibration damping properties of the subgrade at the main area of the sole of a ballast prism of normalized thickness, a protective sand cushion and clay soils under conditions of harmonic vibrations on the basis of physical and chemical mechanics. It was noted that the Kelvin-Vogt model, currently used for modeling, is not applicable for layered systems that do not have, in principle, concentrated masses. For the occurrence of oscillations in the clay layer, it is necessary that under it there would be a medium reflecting the vertical longitudinal wave. Otherwise, the reverse half-wave will not form, and the compression wave will go deep into the ground and turn into heat in the end. Such problems can be solved only using the theory of wave processes. On the basis of the harmonic analysis of wave processes in layered systems for the ballast track, it is shown that the displacement amplitude at the sand-loam boundary decreases 26 times in the frequency range 1-250 Hz. Along the sleeper, secondary longitudinal and transverse waves arise due to the “transfer” of the energy of the main longitudinal wave into the transverse along the sleepers. As a result, circulation flows along the length of the sleeper occurred as well as irreversible deformation of the prism and the accumulation of defects in the subgrade, the porosity and the probability of splashes of ballast are increased. The best damping and cost properties have constructions with crushed stone in comparison with a ballastless design. However, the stability of the motion on the ballast prism and its inter-repair period depends on the correct organization of drains, especially in spring and autumn. Developed apparatus for determining the degree of stress damping in the structure of the track subgrade and the superstructure can be used to develop a normative document for selecting the design of the subgrade structure of the track, depending on the geological, climatic conditions and the average annual groundwater level. The use of the apparatus of linear harmonic analysis is explained by the fact that the influence of nonlinear effects of wave propagation in dispersed materials does not have time to appear because of the extremely small thicknesses of materials constituting the subgrade.